PENGARUH KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN MOTIVASI TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA ( Studi pada Guru SMA Negeri kelompok Sub Rayon 02 Kota Semarang ) (Students' Journal of Economic and Management, 2013)
This study is intended to examine and analyze the effect of managerial ability of the principal and motivation teachers performance with job satisfaction mediation of teachers in sub - district 02 Semarang. The type of this study is field study (field research) with quantitative approach. The population of this study who teach at state senior high schools in sub – district 02 Semarang. Samples are used proportional random sampling used 129 teachers. Linear regression analysis model used adjusted R-square, F-test, t-test, and path analysis. The result of this study shows that; (1) The principals managerial ability han’t positive significant effect on job satisfaction. (2) Motivation has positive significant effect on job satisfaction. (3) The principals managerial ability has positive significant effect on the teachers performance. (4) Motivation hasn’t positive significant on teacher performance. (5) Job satisfaction hasn’t positive significant effect on teacher performance.   Keywords: principal managerial ability,  job satisfaction, and teacher performance